Factors Associated with Malnutrition in Adolescent Girls during the COVID-19 Pandemic - Aisyah, Iseu Siti; Yunianto, Andi Eka; Neni, Neni (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to analyze the factors associated with malnutrition in adolescent girls. The study design was a cross-sectional study with a stratified proportional random sampling, which resulted in samples of 156 adolescent girls aged 10 to 24 years in high schools in Tasikmalaya City. Chi-square test is used to analyze factors associated with malnutrition in adolescent girls. Menstrual cycle, knowledge, physical activity, and stress were significantly associated with malnutrition, while a history of infectious disease was not significantly associated. The implication of this research is that during the pandemic, adolescent girls need to maintain knowledge, physical activity, and coping skills to avoid malnutrition.